Cyberloafing in the Millennial Generation in Java, Indonesia: Its Role in Mediating the Impact of Work Overload on Performance - Tri Yanuarto Nugroho; Herlina Dyah Kuswanti (UPN Veteran Yogyakarta, 2023)
The millennial generation dominates the workforce at this time. Therefore their performance is important to improve the quality of the company's work. Unfortunately, the millennial generation has a tendency to feel excessive stress at work, especially because the workload is felt to be excessive. This work overload can make the millennial generation have the potential to do cyberloafing as an act of self-relaxation. Therefore, this study examines the mediating role of cyberloafing on the effect of workload on performance in millennial generation employees. The population of this study is the millennial generation on Jaw Island, with a total sample of 218 people. Data were analyzed using the